1999
DOI: 10.1139/w98-214
|View full text |Cite
|
Sign up to set email alerts
|

PKA from Saccharomyces cerevisiae can be activated by cyclic AMP and cyclic GMP

Abstract: Analysis of Saccharomyces cerevisiae genome revealed no sequence homologous to cyclic GMP (cGMP) dependent protein kinase from other organisms. Here we demonstrate that cyclic AMP (cAMP) dependent protein kinase purified from S. cerevisiae was almost equally activated by cAMP and cGMP in 3 x 10(-6) M concentrations of either nucleotide in the presence of Mg2+ ions. Interestingly, if Mn2+ ions were used instead of Mg2+, cGMP was only 30% as effective as cAMP in the activation of cAMP-dependent protein kinase. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…We have shown that phosphorylation of the 58-kDa protein by PKA can also be stimulated by cGMP. These results con¢rmed our earlier observations that native PKA from yeast can be stimulated by cAMP and cGMP [18].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We have shown that phosphorylation of the 58-kDa protein by PKA can also be stimulated by cGMP. These results con¢rmed our earlier observations that native PKA from yeast can be stimulated by cAMP and cGMP [18].…”
Section: Resultssupporting
confidence: 92%
“…Postribosomal cell-free extracts were prepared in bu¡er A containing: 50 mM Tris^HCl pH 7.5, 6 mM 2-mercaptoethanol, 10 mM L-glycerophosphate, 1 mM phenylmethylsulfonyl £uoride (PMSF), 0.5 mM ethylenediaminetetraacetic acid (EDTA) as described previously [18]. Crude PKA preparation was obtained from cell-free extract by ammonium sulfate precipitation at 55% saturation.…”
Section: Puri¢cation Of Yeast Pkamentioning
confidence: 99%
See 1 more Smart Citation
“…7). Experimental evidence indicates that the subunit from Saccharomyces can be activated by both cAMP and cGMP (Cytrynska et al 1999). …”
Section: Familymentioning
confidence: 99%
“…The second messenger cAMP is well known to activate PKA by binding to regulatory subunits. Although, little is known regarding cGMP binding to bovine PKA, PKA is activated by both cAMP and cGMP in Orconectus limosis, Amblyomma americanum, Saccharomyces cerevisiae, and Pichia pastoris [20][21][22][23]. We find that both cAMP and cGMP bind to bovine PKA, with a preference for cAMP.…”
Section: Application Of Cofactor Fingerprinting With Std Nmr Inmentioning
confidence: 81%